The Mental Set in Classroom Management During Distance Learning - Kusumawardani, Dinda Khamaril; Rahmajanti, Sri (Graduate School of Universitas Negeri Malang, 2023)
This paper aims to reveal the English teachers’ beliefs about their classroom management during distance learning. Moreover, this study also presented the solution that the expert teachers gave to conquer those difficulties. This study involved big number of participants and presented the solution, therefore the descriptive survey research design was chosen. A questionnaire and interview used to collect data in which the items were taken from three books related to Classroom Management. The findings showed that the English teachers found difficulties in the aspect of Mental Set. Related to those difficulties several suggestions were provided. The solutions were related to how the English teachers’ dealt with burnout and anxiety, inappropriate emotions, etc.